Pengaruh Gaya Hidup, Fomo, Literasi Keuangan Syariah, dan Persepsi Risiko Terhadap Keputusan Investasi Cryptocurrency - Hanif, Hilman; Harahap, Muhammad Ikhsan; Silalahi, Purnama Ramadhani (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to understand how Lifestyle, FOMO, Sharia Financial literacy, and Risk Perception influence Cryptocurrency Investment Decisions (Crypto Academy Case Study). Data was collected through questionnaires distributed to 100 selected respondents using purposive sampling. Quantitative methods are used with Structural Equation Model (SEM) analysis with the Smart PLS version 4 application for analysis. This study aims to analyze the influence of various factors on investment decisions, focusing on lifestyle, the FOMO phenomenon, Islamic financial literacy, and risk perception. The analysis results show that not all independent variables have a significant effect on investment decisions. Lifestyle (X1) has a p-value of 0.148 and a t-statistic of 1.446, which indicates that the effect is not significant with a small f-square value of 0.026. The FOMO phenomenon (X2) also shows a trend with a p-value of 0.069 and a t-statistic of 1.817, but remains insignificant, with an f-square value of 0.039. Islamic financial literacy (X3) shows a p-value of 0.798 and a t-statistic of 0.257, and a very low f-square value of 0.001, indicating no significant effect. In contrast, risk perception (X4) is shown to have a significant influence on investment decisions with a p-value of 0.012 and a t-statistic of 2.514, as well as a higher f-square value of 0.104. This finding confirms that risk perception is an important factor that can positively influence investment decisions. Overall, only risk perception shows a significant relationship with investment decisions, while other factors do not have a meaningful impact in this context.